2010
DOI: 10.1002/clen.201000246
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ammonia, Hydrogen Sulfide, and Short‐Chain Fatty Acids Emission during the Sewage Sludge Composting

Abstract: The effect of mature compost (MC) used as a bulking agent on ammonia, hydrogen sulfide, and short-chain fatty acids emission reduction during sewage sludge (SS) composting process was studied in this paper. Three types of mixtures, single SS, SS þ wood chips (SS þ WC), and SS þ MC, were composted in a laboratory reactor. Among the different treatments, decrement rates of NH 3 emission (based on initial TN) from SS to SS þ MC and SS þ WC to SS þ MC were 63 and 59%, respectively. The H 2 S concentration ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Comparing to what has been observed in other RS composting studies (Rosenfeld et al, 2004;Pagans et al, 2006), similar maximum concentrations were found when material temperature was nearly 60ºC, whereas similar minimum concentrations were measured when material temperature dropped to mesophilic conditions. On the other hand, for the curing phase of pile 2 -which was always in mesophilic conditions-the maximum and minimum values registered in the gaseous emissions were 20 ppmv and 0.5 ppmv, respectively, which are lower than what has been found in similar works (Rosenfeld et al, 2004;Chen and Xin-Wu, 2010). There is a great difference between the emission rates observed in piles 1 and 2, indicating that ammonia emission is dependent on material's temperature, what fits…”
Section: Accepted Manuscriptmentioning
confidence: 52%
“…Comparing to what has been observed in other RS composting studies (Rosenfeld et al, 2004;Pagans et al, 2006), similar maximum concentrations were found when material temperature was nearly 60ºC, whereas similar minimum concentrations were measured when material temperature dropped to mesophilic conditions. On the other hand, for the curing phase of pile 2 -which was always in mesophilic conditions-the maximum and minimum values registered in the gaseous emissions were 20 ppmv and 0.5 ppmv, respectively, which are lower than what has been found in similar works (Rosenfeld et al, 2004;Chen and Xin-Wu, 2010). There is a great difference between the emission rates observed in piles 1 and 2, indicating that ammonia emission is dependent on material's temperature, what fits…”
Section: Accepted Manuscriptmentioning
confidence: 52%
“…However, [42] evaluated the OEFs of different substrates in a 300 L aerated pilot-scale reactor, reporting an OEF of 9.35 × 10 8 ou•Mg −1 DM-SS for SS composting and [24] obtained an OEF of 9.45 × 10 7 ou•Mg −1 DM-SS in a full-scale sewage sludge composting plant. For SS composting, different ranges of target pollutants and odour concentrations can be found in literature depending on the characteristics of the feedstocks or the composting process itself [43][44][45]. Figure 4 shows the daily odour emission rates (OER) obtained during the SS composting process, together with the average temperature of the reactor and the specific airflow.…”
Section: Nh 3 H 2 S Tvocs and Odour Emissionmentioning
confidence: 99%
“…Even though the application of sewage sludge in the farm land recycles the essential nutrients, their continuous direct application may result in accumulation of potential toxic elements. [23][24][25] Nonetheless, it is widely accepted that around 35-40% of sewage-sludge-derived-compost guaranteed for healthy soil conditioning and serving as economical fertilizer for selective plant species without risk of contamination. [26] Considering these two scenarios of sludge application in agriculture, it is imperative to assess the profound impact of transport of nutrients, as well as potential immobilization of toxic compounds from such recirculating leachate in the porous media due to the possible physicochemical interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the application of sewage sludge in the farm land recycles the essential nutrients, their continuous direct application may result in accumulation of potential toxic elements. [ 23–25 ] Nonetheless, it is widely accepted that around 35–40% of sewage‐sludge‐derived‐compost guaranteed for healthy soil conditioning and serving as economical fertilizer for selective plant species without risk of contamination. [ 26 ]…”
Section: Introductionmentioning
confidence: 99%